Occupational respiratory disorders in Iran: a review of prevalence and inducers - Beigoli, Sima; Amin, Fatemeh; Kazemi Rad, Hamideh; Rezaee, Ramin; Boskabady, Mohammad Hossein (Frontiers in Medicine, 2024)
The link between occupational respiratory diseases (ORD) and exposure to harmful factors that are present in the workplace has been well shown. Factors such as physical activity, age and duration of occupational exposure playing important roles in ORD severity, should be identified in the workplace, their effects on workers health should be studied, and ultimately, exposure to them must be minimized.We carried out a literature review by searching PubMed, Scopus, and Web of Science databases to retrieve studies published from 1999 until the end of April 2023 reporting the prevalence and inducers of ORD in Iran.In Iranian workers, several ORD such as interstitial lung disease, silicosis, occupational asthma, pulmonary inflammatory diseases, chronic obstructive pulmonary diseases, and lung cancers have been reported. It was indicated that ORD mainly occur due to repeated and prolonged exposure to noxious agents in the workplace. We also extracted the prevalence of ORD in different regions of Iran from the retrieved reports.Based on our literature review, the prevalence of ORD among Iranian workers highlights the importance of regular assessment of the risk of exposure to noxious agents in the workplace to develop measures for preventing potential adverse effects.